Participant retention in follow-up studies of prematurely born children - Victoria MacBean; Simon B. Drysdale; Sanja Zivanovic; Janet L. Peacock; Anne Greenough (BMC, 2019)
Abstract Background Follow-up studies of infants born prematurely are essential to understand the long-term consequences of preterm birth and the efficacy of interventions delivered in the neonatal period. Retention of participants for follow-up studies, however, is challenging, with attrition rates of up to 70%. Our aim was to examine retention rates in two follow-up studies of prematurely born children and identify participant or study characteristics that were associated with higher attrition, and to discuss retention strategies with regard to the literature. Methods Data from children recruited at birth to one of two studies of prematurely born infants were assessed. The two studies were the United Kingdom Oscillation Study (UKOS, a randomised study comparing two modes of neonatal ventilation in infants born less than 29 weeks of gestational age (GA)), and an observational study examining the impact of viral lower respiratory tract infections in infancy in those born less than 36 weeks of GA (virus study). The UKOS participants, but not those in the virus study, had regularly been contacted throughout the follow-up period. UKOS subjects were followed up at 11 to 14 years of age and subjects in the virus study at 5-7 years of age. At follow up in both studies, pulmonary function and respiratory morbidity were assessed. Retention rates to follow-up in the two studies and baseline characteristics of those who were and were not retained were assessed. Results Retention was significantly higher in UKOS than the virus study (61% versus 35%, p < 0.0001). Subjects lost to UKOS follow up had greater deprivation scores (p < 0.001), a greater likelihood of intrauterine tobacco exposure (p = 0.001) and were more likely to be of non-white ethnicity (p < 0.001). In the virus study, those lost to follow-up had higher birth weights (p = 0.036) and were less likely to be oxygen dependent at hospital discharge (p = 0.003) or be part of a multiple birth (p = 0.048). Conclusions Higher retention was demonstrated when there was regular contact in the follow-up period. Both social factors and initial illness severity affected the retention into follow-up studies of prematurely born infants, though these factors were not consistent across the two studies.